Pengaruh Perceived Quality, Brand Trust, dan Customer Experience terhadap Repurchase Intention pada Produk Skincare Scarlett di DKI Jakarta - Darryl Sagara; Nadya Fadillah F; Daru Putri Kusumaningtyas (Indo Publishing, 2026)
This study aims to analyze the influence of Perceived Quality, Brand Trust, and Customer Experience on Repurchase Intention among consumers of Scarlett skincare products in Jakarta. This study employed a quantitative approach using a survey method through the distribution of questionnaires to respondents who met the research criteria. The sample consisted of 155 Generation Z respondents aged 18–29 years who had used or purchased Scarlett products in Jakarta. The sampling technique used was non-probability sampling with a purposive sampling method. The data were analyzed using the Statistical Package for the Social Sciences (SPSS), including descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results showed that Perceived Quality had a positive and significant effect on Repurchase Intention, Brand Trust had a positive and significant effect on Repurchase Intention, and Customer Experience had a positive and significant effect on Repurchase Intention. Simultaneously, Perceived Quality, Brand Trust, and Customer Experience also had a positive and significant effect on Repurchase Intention. The three variables explained 58.1% of the variation in Repurchase Intention, while the remaining 41.9% was explained by other factors outside the research model. These findings indicate that consumers’ perceptions of product quality, trust in the brand, and experiences gained through interactions with the product are important aspects in shaping consumers’ intention to repurchase Scarlett products.